Ancestry Estimation Based on Morphoscopic Traits in a Sample of African Slaves from Lagos, Portugal (15th-17th Centuries) - Coelho, C. (2017)
In 2009, a skeletal collection of 158 individuals was excavated in Valle da Gafaria, Lagos, Portugal. These individuals were buried in an unusual way, having been discarded in an urban dump located outside the medieval city walls, dated from the 15th-17th centuries. Lagos was, at the time, an important slave trade harbour, and during the excavation, the morphological appearance of the skulls and the presence of intentionally modified teeth in some individuals raised suspicion that they were African slaves. Despite the extensive historical information about the Atlantic slave trade, so far skeletal remains identified as slaves were scarce, especially in Europe. The aim of the present study is to estimate the ancestry of a sample of 33 adult individuals (28 females and 5 males) recovered in the Valle da Gafaria applying the eleven morphological characteristics recommended by Hefner (2009) using the naïve Bayes classifier. When comparing the individuals with four groups of classification (European, African, American Indian, and Asian), 24 (72.7%) specimens were classified as Africans with a posterior probability greater than 0.90. When only two groups were considered (the African and the European), 31 (93.9%) individuals were classified as Africans with a posterior probability greater than 0.90. These results are in accordance with the historical record and previous genetic studies suggesting that this sample represents a rare archaeological sample of great interest to the history of the Atlantic slave trade, i.e., the Lagos individuals were probably of African ancestry. Although the ancestry is a parameter of the biological profile mainly estimated in forensic Anthropology, this study confirms the importance of its investigation in past populations.